Pengaruh Zat Aditif EP dan ER terhadap Efisiensi Bahan Bakar Kendaraan Bermotor Berdasarkan Specific Fuel Consumption (SFC) - Muchammad Chusnan Aprianto; Kiki Yusuf Irawan; Nurobiyanto (LPPM, Sekolah Tinggi Teknologi DR. KHEZ Muttaqien, 2021)
This study aims to determine the effect of adding EP and ER additives on the efficiency of motor vehicles. The indicator used as fuel efficiency is the Specific Fuel Consumption (SFC). The fuel used is RON 90, RON 92, RON 95 on a 4 stroke engine type. Each fuel is then added with EP and ER additives and is run on a 4 stroke engine. After being tested, the torque, revolutions per minute (rpm), and SFC were calculated. The results showed that the lowest SFC value for the addition of ER additives at RON 92 was 0.093.